Problemática psicosocial y educacional de los niños marginados - Dongo Montoya, Adrián (2011)
The marginalized children’s psychosocial and educational issues, in this essay, are referred to the theoretical debate upon knowledge development and the possible solutions for those children.This issue will be addressed through the analysis of structures or forms of knowledge organization and from the necessary differentiation of social and individual cognitive development. Based on these objectives, we will analyzethe classical theoriesrelated to cognitive developmentofdisadvantaged children, discussindividual andsocialcognitive developmentand, based on our empirical research, postulatean explanationforthese children’s cognitive development. Finally we will discuss and propose some educational solutions.